2019
DOI: 10.15288/jsad.2019.80.32
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cannabis-Specific Parenting as a Mechanism of the Intergenerational Transmission of Cannabis Use and Cannabis Use Disorder

Abstract: Parental cannabis use disorder (CUD) is a known risk factor in the development of adolescent cannabis use. One potential mechanism is parenting behaviors. This study considered cannabis-specific parenting strategies as a mechanism of the relation between parental CUD and adolescent cannabis use. Method: Pathways were examined using multilevel longitudinal mediation models (N = 363, mean age = 16.3 years) comparing adolescent offspring of parents who never used cannabis, parents who used cannabis without CUD, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…Thus, seeing negative maternal consequences of drinking could lead an adolescent to believe that these effects are not so bad or out of the ordinary. Interestingly, similar findings have also been reported in studies of parental substance‐specific communication about alcohol and cannabis (Handley and Chassin, ; Sternberg et al, ). Specifically, Handley and Chassin () found that maternal sharing of her own negative experiences with alcohol was associated with greater alcohol use initiation in a sample of high‐risk adolescents.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, seeing negative maternal consequences of drinking could lead an adolescent to believe that these effects are not so bad or out of the ordinary. Interestingly, similar findings have also been reported in studies of parental substance‐specific communication about alcohol and cannabis (Handley and Chassin, ; Sternberg et al, ). Specifically, Handley and Chassin () found that maternal sharing of her own negative experiences with alcohol was associated with greater alcohol use initiation in a sample of high‐risk adolescents.…”
Section: Discussionsupporting
confidence: 81%
“…Handley and Chassin () suggested that mothers discussing their negative experiences with alcohol may actually be enticing rather than a warning against alcohol use, which may decrease negative views and increase positive views of alcohol. Sternberg and colleagues () reported similar findings concerning disclosure of cannabis‐specific negative experiences, with more parental disclosure predicting more cannabis use in adolescents. Thus, discussing parents’ discussing their negative experiences with alcohol and cannabis did not deter adolescents from drinking or using cannabis.…”
Section: Discussionmentioning
confidence: 75%
“…However, one study did not find parental monitoring to be a significant mediator of the link from maternal heavy alcohol use to young adult problem drinking [ 54 ]. Two other studies found that cannabis-specific and alcohol-specific parenting (sharing of negative experiences and efforts to prevent adolescent use) did not mediate the relationship between parental alcohol or cannabis use disorder and adolescent alcohol or cannabis use [ 55 , 58 ]. Finally, two studies failed to find significant mediation for parental attachment [ 27 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies testing the effects of alcohol-specific and marijuana-specific parenting (i.e., discussing the negative effects of alcohol and marijuana) and the effects of observable parent negative consequences (e.g., a parent getting arrested) identified iatrogenic effects of each on alcohol outcomes. That is, discussing the negative outcomes of substance use with a parent and observing negative consequences in a parent were associated with heightened (rather than dampened) risk for alcohol problems (Handley & Chassin, 2013; Sternberg et al, 2019; Waddell et al, 2020).…”
mentioning
confidence: 99%